Training for aerobic improvements - Richards, R. (1998)
"Training at maxVO2 may, or may not, be the best methodology" - factors such as age, maturity (and associated differences by sex), genetic potential, training environment, and lifestyle all have a profound influence on the end result of a training program. That's why any two swimmers in the same program will most likely react differently. Questions: - What is aerobic capacity? - Aerobic Power or Aerobic Capacity - What's the Difference? - Training to Improve Aerobic Capacity and Power